Immunomodulatory effect of an isolated fraction from Tinospora crispa on intracellular expression of INF-γ, IL-6 and IL-8 - Abood, W.N. (BioMed Central, 2014)
Background Immunomodulators are substances that modify immune system response to a threat. Immunomodulators modulate and potentiate the immune system, keeping it highly prepared for any threat. The immunomodulatory effect of the traditional medicine Tinospora crispa is investigated in this work.